2016
DOI: 10.21577/1984-6835.20160124
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Composition and Biological Activities of the Essential Oils from the Fresh Leaves of Citrus limonia Osbeck and Citrus latifolia Tanaka (Rutaceae)

Abstract: Artigo Composição Química e Atividades Biológicas dos Óleos Essenciais das Folhas Frescas de Citrus limonia Osbeck e Citrus latifolia Tanaka (Rutaceae)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 12 publications
0
17
0
1
Order By: Relevance
“…The high leishmanicidal activity of the essential oil from leaves of C. aschersoniana may be related to the presence of the chemical components limonene (42.3%), linalool (9.7%) and nerolidol (8.6%), which are the major constituents in the essential oil studied and with anti-Leishmania activity already known (Arruda et al 2005, Graebin et al 2010, Camargo and Vasconcelos 2014. Limonene has also been previously reported as the compound responsible for the leishmanicidal activity exhibited by the essential oils of Citrus limonia and Citrus latifolia (Estevam et al 2016). The leishmanicidal potential of the linalool was already reported in the literature against promastigote and amastigote forms of L. amazonensis (LD 50 of 4.3 ng/mL and 15.5 ng/ mL, respectively) (Camargo and Vasconcelos 2014).…”
Section: Resultsmentioning
confidence: 79%
“…The high leishmanicidal activity of the essential oil from leaves of C. aschersoniana may be related to the presence of the chemical components limonene (42.3%), linalool (9.7%) and nerolidol (8.6%), which are the major constituents in the essential oil studied and with anti-Leishmania activity already known (Arruda et al 2005, Graebin et al 2010, Camargo and Vasconcelos 2014. Limonene has also been previously reported as the compound responsible for the leishmanicidal activity exhibited by the essential oils of Citrus limonia and Citrus latifolia (Estevam et al 2016). The leishmanicidal potential of the linalool was already reported in the literature against promastigote and amastigote forms of L. amazonensis (LD 50 of 4.3 ng/mL and 15.5 ng/ mL, respectively) (Camargo and Vasconcelos 2014).…”
Section: Resultsmentioning
confidence: 79%
“…The chemical composition and biological properties of many essential oils have drawn the interest of researchers who have studied them widely in several areas (Estevam et al 2016). In the literature, previous studies of essential oils from other species of the genus Protium showed similar chemical composition to the one found by this study.…”
Section: Resultsmentioning
confidence: 99%
“…The trypanocidal activity of the essential oil from P. ovatum leaves is described by this paper for the first time. The literature describes that samples with IC 50 < 10 μg.mL -1 had highly active trypanocidal activity, whereas others were active (IC 50 > 10 < 50 μg.mL -1 ), moderately active (IC 50 > 50 < 100 μg.mL -1 ) and inactive (IC 50 > 100 μg.mL -1 ) (Estevam et al 2016). …”
Section: Resultsmentioning
confidence: 99%
“…Species of the genus Citrus have been highlighted because they are rich in essential oils which are very versatile and often used as flavorings in several goods, such as beverages, soaps, cosmetics and household products. Their essential oils have also been frequently used in medical treatments due to their antimicrobial, antifungal, antibacterial and antiparasitic properties (Estevam et al 2016). Many recent studies that have attempted to determine the chemical composition of essential oils extracted from C. aurantifolia.…”
Section: Introductionmentioning
confidence: 99%